1983
DOI: 10.1128/aem.46.6.1417-1419.1983
|View full text |Cite
|
Sign up to set email alerts
|

Heat injury in Staphylococcus aureus 196E: protection by metabolizable and non-metabolizable sugars and polyols

Abstract: Polyols and sugars, which were not metabolized (02 uptake or fermentation was not demonstrated), protected Staphylococcus aureus 196E against heat injury as well as metabolized compounds. Inhibitors of glucose metabolism decreased 02 uptake with glucose but did not affect the protective ability of glucose against heat injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1984
1984
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 17 publications
1
2
0
Order By: Relevance
“…As shown in Figure 1, cells grown in TSB medium and subsequently heated in TSB medium containing either 10% NaCl or 15% KCl had a greater thermal tolerance than cells heated in TSB medium containing no added solutes. These results are consistent with those re-ported previously by other investigators who have demonstrated that the a w of the heating menstruum can have an important influence on the thermal tolerance of bacterial cells (7,9,16,(32)(33)(34)38).…”
Section: Resultssupporting
confidence: 93%
“…As shown in Figure 1, cells grown in TSB medium and subsequently heated in TSB medium containing either 10% NaCl or 15% KCl had a greater thermal tolerance than cells heated in TSB medium containing no added solutes. These results are consistent with those re-ported previously by other investigators who have demonstrated that the a w of the heating menstruum can have an important influence on the thermal tolerance of bacterial cells (7,9,16,(32)(33)(34)38).…”
Section: Resultssupporting
confidence: 93%
“…Whether this represents differences between gram-negative and grampositive bacteria or differences in the mechanism(s) of heat damage in the two organisms is not known. The exact mechanism by which these solutes prevent heat injury in S. aureus is not known (15)(16)(17).…”
Section: Resultsmentioning
confidence: 99%
“…The mechanism involved in this protection is not fully clear. It is well known that cells suspended in a high-osmolarity medium suffer from a rapid loss of intracellular water (this phenomenon is called plasmolysis), and that the heat stability of proteins increases in media of low a w [ 72 , 120 ]. It has also been suggested that sucrose could interact with membrane phospholipids, increasing the membrane’s heat stability [ 121 ].…”
Section: Factors Affecting Bacterial Inactivationmentioning
confidence: 99%